ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN KETIDAKNYAMANAN SERING BAK - Ika Putri Damayanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Pregnancy is the period beginning on the meeting between the egg and sperm cells and then develop into a zygote and continues to be a fetus. Pregnant women are very important to conduct early ANC to the nearest health workers to detect the risk of pregnancy or pregnancy complications. Methods of midwifery care aims to quality of life of pregnant women to detect complications early in the third trimester of physical changes that cause discomfort and frequent urinating frequently interfere with rest mother. This care study was conducted in BPM Putri Asih Pekanbaru and also go home visits to patients at Jl. Surabaya began on 07 to 23 June 2018. This care is done with the approach and documentation SOAP method. Care that obtained midwifery care running smoothly without complication. In the results obtained from the data collection did not find the gaps with the theory.